Genome-wide identification and characterization of InDels and SNPs in Glycine max and Glycine soja for contrasting seed permeability traits - Ramakrishna, G. (BMC Plant Biol, 2018)
BACKGROUND: Water permeability governed by seed coat is a major facet of seed crops, especially soybean, whose seeds lack physiological dormancy and experience rapid deterioration in seed viability under prolonged storage. Moreover, the physiological and chemical characteristics of soybean seeds are known to vary with seed coat color. Thus, to underpin the genes controlling water permeability in soybean seeds, we carried out an in-depth characterization of the associated genomic variation. RESULTS: In the present study, we have analyzed genomic variation between cultivated soybean and its wild progenitor with implications on seed permeability, a trait related to seed storability. Whole genome resequencing of G.max and G. soja, identified SNPs and InDels which were further characterized on the basis of their genomic location and impact on gene expression. Chromosomal density distribution of the variation was assessed across the genome and genes carrying SNPs and InDels were characterized into different metabolic pathways. Seed hardiness is a complex trait that is affected by the allelic constitution of a genetic locus as well as by a tricky web of plant hormone interactions. Seven genes that hold a probable role in the determination of seed permeability were selected and their expression differences at different stages of water imbibition were analyzed. Variant interaction network derived 205 downstream interacting partners of 7 genes confirmed their role in seed related traits. Interestingly, genes encoding for Type I- Inositol polyphosphate 5 phosphatase1 and E3 Ubiquitin ligase could differentiate parental genotypes, revealed protein conformational deformations and were found to segregate among RILs in coherence with their permeability scores. The 2 identified genes, thus showed a preliminary association with the desirable permeability characteristics. CONCLUSION: In the light of above outcomes, 2 genes were identified that revealed preliminary, but a relevant association with soybean seed permeability trait and hence could serve as a primary material for understanding the molecular pathways controlling seed permeability traits in soybean. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1341-2) contains supplementary material, which is available to authorized users.